Remanso fluvial, Río Fucha (2017)
Presented in this document is a summary of all the analytical, investigative and design works which were developed along the semester in the Advanced Unit 201710. The main of this work was the development of the station NQS in the line of Bogota's new Metro, located in Av 30, Str 8 South. In addition to the metro station, a sports complex was designed as a complementary use of the station plaza. This would bring recreational and health benefits to the population as well as enhancing the surroundings and the ecological structure.--Tomado del Formato de Documento de Grado.